1991
DOI: 10.1176/jnp.3.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetic resonance imaging in Rett syndrome

Abstract: Rett syndrome (RS) is a progressive neurological disorder of females, characterized by the early onset of autistic behavior, ataxia, and "handwringing" movements. The present magnetic resonance imaging study was undertaken with the purpose of investigating whether structural brain abnormalities of RS patients are similar to those recently reported in autism. The subject population consisted of eight patients and an equal number of age- and sex-matched controls. Area and shape measurements were taken at selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Additionally, it has long been known that RTT females display microcephaly on a gross anatomic scale, with brain volume generally being reduced by 25% (57–59). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has long been known that RTT females display microcephaly on a gross anatomic scale, with brain volume generally being reduced by 25% (57–59). …”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies of RTT subjects demonstrate decreased cerebral volumes (Carter et al, 2008; Jellinger, 2003; Murakami, Courchesne, Haas, Press, & Yeung-Courchesne, 1992), with reductions in caudate nucleus, cortical, and midbrain volumes disproportionately reduced compared to other structures (Casanova et al, 1991; Dunn et al, 2002; Reiss et al, 1993; Subramaniam, Naidu, & Reiss, 1997). PET imaging studies demonstrate specific changes in BG transmitter function.…”
Section: Diseases and Links To Striatal Dysfunctionmentioning
confidence: 99%
“…As regards cortical WM, mild and diffuse reductions have been previously reported and linked to axonal pathology (50). Notably, studies in this field have selectively shown decreased volumes of the cerebrum, cerebellum, and caudate nucleus (43,44,(50)(51)(52)(53). Surface-based morphological approaches, including cortical gyrification and regional cortical thickness evaluation, have not been fully explored.…”
Section: Morphologic Mri In Rtt With Mecp2 Mutationmentioning
confidence: 99%